What Elements of Successful Scientific Theories Are the Correct Targets for "Selective" Scientific Realism?. Issue 3 (July 2014) - Peters, Dean
Abstract : Selective scientific realists disagree on which theoretical posits should be regarded as essential to the empirical success of a scientific theory. A satisfactory account of essentialness will show that the (approximate) truth of the selected posits adequately explains the success of the theory. Therefore, ( a ) the essential elements must be discernible prospectively; ( b ) there cannot be a priori criteria regarding which type of posit is essential; and ( c ) the overall success of a theory, or 'cluster' of propositions, not only individual derivations, should be explicable. Given these desiderata, I propose a "unification criterion" for identifying essential elements.